Real-World Primary Resistance to First-Line Immune-Based Combinations in Patients with Advanced Renal Cell Carcinoma (ARON-1) - Santini, Daniele; Li, Haoran; Roviello, Giandomenico; Park, Se Hoon; Grande, Enrique; Kucharz, Jakub; Basso, Umberto; Fiala, Ondrej; Monteiro, Fernando Sabino Marques; Poprach, Alexandr; Buti, Sebastiano; Molina-Cerrillo, Javier; et al. (Targeted oncology, 2024)
BACKGROUND: Therapeutic advancements based on immuno-oncology combinations have revolutionized the management of patients with renal cell carcinoma. However, patients who have progressive disease as the best response, "primary refractory" (Pref), face dismal outcomes. OBJECTIVE: Our multicenter retrospective real-world study aims to assess the prevalence and clinicopathological characteristics of Pref patients. METHODS: This study collected data from 72 centers across 22 countries (1709 patients), involving patients aged ≥18 years with metastatic clear cell renal cell carcinoma. All patients were treated with first-line immune-oncology combinations. Data included patient demographics, histology, metastatic sites, and treatment responses. Radiological assessments followed Response Evaluation Criteria in Solid Tumors version 1.1. Statistical analyses employed Kaplan-Meier method, Cox proportional hazard models, logistic regression, and the receiver operating characteristic curve. RESULTS: In our study, the Pref rate was 19%. Nivolumab/ipilimumab showed the highest Pref rate (27%), while pembrolizumab/lenvatinib exhibited the lowest (10%). Primary refactory patients demonstrated significantly lower median overall survival (7.6 months) compared with non-Pref patients (55.7 months), p < 0.001. At the multivariate analysis, nephrectomy, sarcomatoid de-differentiation, intermediate/poor International Metastatic RCC Database Consortium risk, and bone and brain metastases emerged as significant predictors of overall survival for Pref patients with renal cell carcinoma. Logistic regression showed a significant relationship between liver metastases, intermediate/poor International Metastatic RCC Database Consortium risk, and no surgery and an increased risk of Pref. This study presents limitations, mainly because of its retrospective design. CONCLUSIONS: The ARON-1 study provides valuable insights into Pref patients, emphasizing the challenges of this precociously resistant subgroup. Identified predictors could guide risk stratification, aiding clinicians in tailored therapeutic approaches.
Keywords: senioři; Male; Female; Drug Resistance, Neoplasm; Aged; Middle Aged; Carcinoma, Renal Cell; mužské pohlaví; Kidney Neoplasms; ženské pohlaví; Adult; karcinom z renálních buněk; Retrospective Studies; senioři nad 80 let; retrospektivní studie; dospělí; chemorezistence; lidé středního věku; Aged, 80 and over; nádory ledvin; lidé; Humans